Emission factors of carbonaceous particulate matter and polycyclic aromatic hydrocarbons from residential solid fuel combustions - Shen, Guofeng (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
Emission inventory is basic for the understanding of environmental behaviors and potential effects of compounds, however, current inventories are often associated with relatively high uncertainties. One important reason is the lack of emission factors (EFs), especially for the residential solid fuel combustion in developing countries. In the present study, emission factors of a group of pollutants including particulate matter, organic carbon, elemental carbon (sometimes known as black carbon) and polycyclic aromatic hydrocarbons were measured for a variety of residential solid fuels including coal, crop straw, wood, and biomass pellets in rural China. The study provided a large number of emission factors that can be further used in emission estimation. Composition profiles and isomer ratios were investigated and compared so as to be used in source apportionment. In addition, the present study identified and quantified the influence of factors like fuel moisture, volatile matter on emission performance. The publication of the study will be of interest and helpful to the readers in the field of air pollution, human health, fuel saving and energy consumption etc. Guofeng Shen works at the Institute of Atmospheric Sciences, Jiangsu Academy of Environmental Sciences, China.